Genetic Probe Enhanced MRI: Enhancing Prostate‐Cancer‐Specific MRI by Genetic Amplified Nanoparticle Tumor Homing (Adv. Mater. 30/2019). Issue 30 (23rd July 2019) - Zhao, Yang; Peng, Jing; Yang, Jinyi; Zhang, Enlong; Huang, Ling; Yang, Hong; Kakadiaris, Eugenia; Li, Jingjin; Yan, Bin; Shang, Zhiqun; Jiang, Ning; Zhang, Xuening; et al.
Abstract : In article number1900928, Gang Han, Yuanjie Niu, and co‐workers develop a prostate‐cancer‐specific genetic approach toward amplified MRI nanoparticles tumor homing. This strategy addresses the unmet key clinical need in MR imaging of ultrasmall prostate cancer lesions. This concept is highly translatable and is expected be able to be implemented in numerous other nanoscale systems and tumor‐specific biomarkers in the near future.